Family Albums and Victorian Scrapbooks. Feminism and Photography in the mid-19 Century (L'uomo nero. Materiali per una storia delle arti della modernità, 2023)
In the Victorian context of the mid-nineteenth century, the possibility of buying and collecting small and cheap photographic portraits gave life to the fashion of making family albums and scrapbooks by juxtaposing photographs with drawings and writings. The aristocratic women who experimented with these practices attributed the strength of an identity and gender politics tool to them, in which body and performativity uncovered the possibility of manipulating the dimensions of space and time in a transgressive way. This essay explores these photographic experiences by examining two case studies in particular: the album of Lady Charlotte Milles (1835-1927), and that of Georgina Berkeley (1831-1919), to give a reading in which the history of photography and contemporary art intertwine with the feminist and gender studies. From this point of view, the recovery of marginal and amateur activities makes it possible to enhance extra-artistic experiences, such as the Victorian scrapbooks, in their early conceptual use of photography. Although such practices were bound to a limited social and historical context, the albums made by Victorian women showed the power of photography in its autobiographical, identity and imaginary meanings, with the aim of negotiating the invisibility to which they were destined but, at the same time, giving life to actions, experiences and ideas that only contemporary art would have made possible.
Keywords: Photography; Feminism; Family Album; Gender Politics; Scrapbook